Analysis of Omnichannel Consumer Behavior: Purchase Intention on Omni-channel Restaurants in Indonesia - Muhammad Elbert Ongko; Sri Rahayu Hijrah Hati (Nusantara Science and Technology Proceedings, 2020)
The advancement of the internet and emerging technology has altered the world of industry through sectors. Additional networks also emerged, altering buying preferences and purchasing behaviour. The omnichannel approach is a modern innovative method of marketing strategy in which, with the use of advanced technologies across networks, it is possible to integrate various channels for shopping to provide customers with a specific and comprehensive shopping experience. There is a disconnect in customers' omnichannel attitudes and businesses' ability to execute an omnichannel approach. The aim of this paper is to define and understand the factors that affect omnichannel consumers' actions during the shopping phase, specifically their adoption and usage of technologies. An initial model was created to explain omnichannel consumer behavior using the variables used in UTAUT2 and other previous research on omnichannel consumer behavior. Structural Equation Modelling was used to test the model on a sample of 495 customers of omnichannel restaurants (SEM). The findings suggest that the following factors significantly affect purchasing intention in an omnichannel context: habit, encouraging circumstances, personal innovativeness, hedonic drive, success expectancy, and social influence.